Prospective and challenges of locally applied repurposed pharmaceuticals for periodontal tissue regeneration - El-Nablaway, Mohammad; Rashed, Fatema; Taher, Ehab S.; Abdeen, Ahmed; Taymour, Noha; Soliman, Magdalen M.; Shalaby, Hany K.; Fericean, Liana; Ioan, Bănățean-Dunea; El-Sherbiny, Mohamed; Ebrahim, Elturabi; Abdelkader, Afaf; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Periodontitis is a persistent inflammatory condition that causes periodontal ligament degradation, periodontal pocket development, and alveolar bone destruction, all of which lead to the breakdown of the teeth's supporting system. Periodontitis is triggered by the accumulation of various microflora (especially anaerobes) in the pockets, which release toxic substances and digestive enzymes and stimulate the immune system. Periodontitis can be efficiently treated using a variety of techniques, both regional and systemic. Effective therapy is dependent on lowering microbial biofilm, minimizing or eradicating pockets. Nowadays, using local drug delivery systems (LDDSs) as an adjuvant therapy to phase I periodontal therapy is an attractive option since it controls drug release, resulting in improved efficacy and lesser adverse reactions. Choosing the right bioactive agent and mode of delivery is the foundation of an efficient periodontal disease management approach. The objective of this paper is to shed light on the issue of successful periodontal regeneration, the drawbacks of currently implemented interventions, and describe the potential of locally delivered repurposed drugs in periodontal tissue regeneration. Because of the multiple etiology of periodontitis, patients must get customized treatment with the primary goal of infection control. Yet, it is not always successful to replace the lost tissues, and it becomes more challenging as the defect gets worse. Pharmaceutical repurposing offers a viable, economical, and safe alternative for non-invasive, and predictable periodontal regeneration. This article clears the way in front of researchers, decision-makers, and pharmaceutical companies to explore the potential, effectiveness, and efficiency of the repurposed pharmaceuticals to generate more economical, effective, and safe topical pharmaceutical preparations for periodontal tissue regeneration.